Empowering Indigenous Communities: The Pursuit of Quality Education and Peaceful Societies - Beverly Laltoog (Inclusive Society and Sustainability Studies, 2024)
Educational Institutions in the Cordillera Administrative Region (CAR) fervently advocate for Indigenous Peoples (IP) and Peace Studies Education in higher learning, aligning with the CHED Regional Memorandum No. 56 of 2023. The University of Baguio and other Higher Educational institutions actively integrate IP and Peace Studies into their academic programs. This paper addresses two objectives: explaining cultural misappropriation and introducing the Cordillera Heritage Project to address this issue. This study utilizes a qualitative-descriptive research method by participating in the different programs under Project Cordillera heritage. Project HERITAGE (Higher Education Regional Integration and Teaching of Appropriate, Genuine, and Exhaustive Studies on Indigenous Peoples) is a collaboration between the University of Baguio, CHED CAR, and regional Higher Education Institutions. It introduces Cordillera Heritage as a foundational course, Cordillera Heritage 101: ‘History and Socio-cultural Heritage’, preserving Cordilleran identity through knowledge, systems, practices, settlements and institutions. The Cordillera Heritage stands as a living legacy, relevant in contemporary society and vital to the region’s history. It culminates in the Cordillera Heritage Workbook, which enhances educational materials and includes faculty immersion and training services. The University of Baguio’s proactive approach earned commendation from the Commission on Higher Education for being the first to offer Cordillera Heritage 101 across all programs. The institution’s commitment reflects in successfully implementing the first regional HERITAGE Faculty Immersion Training Service, showcasing its dedication. The Cordillera Heritage Project responds to regional educational needs by integrating subjects that respect and promote Cordilleran knowledge, values, and culture. Aligned with the aspirations for autonomy and self-determination in Cordillera communities, this course is a significant step toward preserving and promoting the region’s heritage within the educational landscape.